2011
DOI: 10.1007/s11740-011-0316-z
|View full text |Cite
|
Sign up to set email alerts
|

Automation of robotic assembly processes on the basis of an architecture of human cognition

Abstract: A novel concept to cognitive automation of robotic assembly processes is introduced. An experimental assembly cell with two robots was designed to verify and validate the concept. The cell's numerical control-termed a cognitive control unit (CCU)-is able to simulate human information processing at a rule-based level of cognitive control. To enable the CCU to work on a large range of assembly tasks expected of a human operator, the cognitive architecture SOAR is used. On the basis of a self-developed set of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, the number of MTM-1 cycles did not show differences between the deterministic and stochastic part feed. Mayer et al [20] further reported that the desired target state was assembled correctly by the CCU in all 8,400 runs. No assembly errors or deadlocks did occur.…”
Section: Simulation Studymentioning
confidence: 92%
See 2 more Smart Citations
“…However, the number of MTM-1 cycles did not show differences between the deterministic and stochastic part feed. Mayer et al [20] further reported that the desired target state was assembled correctly by the CCU in all 8,400 runs. No assembly errors or deadlocks did occur.…”
Section: Simulation Studymentioning
confidence: 92%
“…No explicit knowledge on how to solve the assembly problem is needed. To validate this approach a simulation environment was developed using a simplified model of the experimental assembly cell consisting of a robot with a gripping device, a queue for part feed, a buffer for part storage and a workplace for the assembly of a target product [20].…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the sequence of fundamental movements (e.g., reach, grasp, move, position, release) is explainable a posteriori, the sequence of parts positioned after another is not predictable a priori due to a lack of elaboration knowledge [22]. Odenthal et al [28] and Mayer et al [29] identified human assembly strategies that were formulated as production rules. When the reasoning component is enriched with these human heuristics, a significant increase of the robot's predictability when assembling the products can be achieved.…”
Section: Journal Of Roboticsmentioning
confidence: 99%
“…However, system designers usually are focused on mechanical automaton in manufacturing systems (Parasuraman et al, 2000), and the limited interest in cognitive automation in manufacturing systems has been directed primarily to assembly systems (Fasth et al, 2011;Lindström and Winroth, 2010;Mayer et al, 2011) or manual material handling (Basile et al, 2012a). Thus, the importance of cognitive automation in material handling systems has not been fully recognized.…”
Section: Introductionmentioning
confidence: 99%